Modern paradigm of the port city of Valparaiso: Dynamic conservation of Historic Urban Landscape (ARQUISUR Revista, 2015)
The Historic Area of the Port City of Valparaiso, declared a UNESCO World Heritage Site on July 2, 2003, was developed from the sixteenth century to be consolidated by a persistent process of modernization in the late nineteenth century, constituting a Historic Urban Landcape, as a result of the transformation that port, commercial and cultural exchange has exercised over their natural resources. The coastal urban edge of the city is one of the most valuable cultural inventions and authenticity, with the potential for sustainable development in the XXI century. However, this landscape is threatened by the dynamics of economic and mediatic globalization, with transnational speculative processes, where urban planning is weak and local, regional and national authorities are unable to take effective control.Landscape preservation of the coastal city of Valparaíso, must be assumed as a dynamic heritage, inserted into a living urban territory, needing to define the measuring indicators the state of conservation and development of this urban-coastal heritage. Their management undertakes a direct assessment of historical roles, the binding participation of social partners, promoting an appropriate architecture, and search for ecological preservation between natural and cultural resources.
Keywords: historic urban landscape; landscape history; urban planning; architecture; heritage conservation